Anthropoesy - Kaur, Raminder (Swiss Journal of Sociocultural Anthropology, 2025)
What might the transformation in transformative anthropology entail? While several responses might be generated, one element that is generally kept to the background is transformation from within. This “inner enquiry” is not necessarily of the self-reflexivity school, nor of decolonizing initiatives, but one that asks for a deep decoloniality of the propertied self along with a deep ethnography with those designated as Other, objects or subjects of the anthropological endeavour. If we do not transform from within, we will continue to retain propertied notions of the self’s relationship to the world, Weltbeziehungen, with their objectified identities, differences and hierarchies both between human, and in relation to non-human lifeforms—which is how the chain-reaction of violences began culminating in the multiple planetary and societal crises of today. In critical response, I propose an anthropoesy—a co-creative conjunction with lifekind.